Dangerous Liaisons: Interests groups and politicians' votes. A Swiss perspective - Stefano Puddu; Martin Péclat (University of Neuchâtel, Institute of Economic Research (IRENE), 2015)
Using a unique dataset, based on the 49th Swiss legislature, we assess lobbying effect on politicians' votes. Counselors' ties are approximated by their mandates in in legal entities. Political representatives' fidelity to their political group is measured by a dummy proximity indicator. We find that proximity increases over time, as the legislature approaches to the end. Furthermore, using alternative techniques, we find that lobbying matters. More precisely, focusing on the econometric results, once controlled for individual features and political groups affiliation, we find that having mandates in energy, banking and insurance, and in the transport sectors reduces counselors' proximity. Finally, we also find that being male, young and being elected in a French or Italian speaking canton negatively affects the proximity measure.
Keywords: D7; H7; 330; Groups of pressure; lobbies; special interests; Swiss Parliament; voting behaviour